Can land value capture make PPP's competitive in fares? A Mumbai case study. (May 2018) - Sharma, Rohit; Newman, Peter
Abstract: Mumbai Metro is planning to build 152 km of high-speed urban rail lines. The first line of Mumbai Metro was built through a Public-Private Partnership (PPP) and opened in 2014. Financial issues since its opening necessitated a fare increase—among one of the highest in India to maintain the line's commercial viability for the private operator. This paper examines how high dependence on farebox revenue could have been avoided by using Land Value Capture (LVC) to finance Mumbai Metro. A panel data hedonic price model was used to assess the impact of Mumbai Metro's commencement on approximately 66, 000 apartments. The model shows a significant uplift of 14% in property prices in the Mumbai Metro catchment area resulting in USD 179 million value capture opportunity under Mumbai's existing legislative framework. This paper suggests that LVC could enable a PPP urban rail projects to achieve financial and social viability if governance systems can enable appropriate mechanisms. Highlights: There is a significant willingness to pay for urban rail in Mumbai. LVC for urban rail can avoid high reliance on farebox revenue and struggles over fare fixation. Panel data HPM shows 14% increase in the value of land around Mumbai Metro. Residential land value increases beyond the traditional 1 km catchment area. LVC could enable a PPP urban rail project to achieve financial and social viability.